A case of thoracoscopic medial basal segmentectomy. (2019) - Kawakita, Naoya; Toba, Hiroaki; Sakiyama, Shoji; Tsuboi, Mitsuhiro; Takizawa, Hiromitsu; Tangoku, Akira
Highlights: Medial basal segmentectomy is uncommon procedure. It is difficult to perform the procedure because of anatomical variations. This is a rare report of thoracoscopic medial basal segmentectomy. Abstract: Introduction: Isolated resection of the medial basal segment (S7) is uncommon because of its small volume, and S7 segmentectomy is considered to be difficult due to anatomical variation. We report a case of successful thoracoscopic S7 segmentectomy. Presentation of case: A 56-year-old man was referred to our hospital with suspected pulmonary metastasis of rectal cancer. A 6-mm nodule was detected in S7. A7 and B7 branched from the basal segmental artery and bronchus, respectively, to run ventral to the inferior pulmonary vein. This made it possible to isolate A7 and B7 by an approach via the interlobar fissure. In addition, V7a and V7b were easily isolated from inferior pulmonary vein. The intersegmental plane was indicated by V7b and was transected along a demarcation line identified by using selective oxygenation via B7. Discussion: B7 most commonly branches from the basal bronchus and A7 from the basal artery to run ventral to the inferior pulmonary vein. With this anatomical type, when the surgeon approaches via the interlobar fissure during surgery, A7 is identified first, B7 is seen behind A7, and the IPV is posterior to B7. Since the intersegmental plane is located ventral to the IPV, segmentectomy can be completed via the interlobar fissure approach. Conclusion: In patients with this pattern of pulmonary artery and bronchial anatomy, isolated S7 segmentectomy is a feasible treatment option.